U-BIOPRED: evaluation of the value of a public–private partnership to industry. Issue 9 (September 2018) - Riley, John H.; Erpenbeck, Veit J.; Matthews, John G.; Holweg, Cecile T.J.; Compton, Christopher; Seibold, Wolfgang; Higenbottam, Timothy; Wagers, Scott; Rowe, Anthony; Myles, David; ,
Highlights: Collaboration between academia, industry and patients. Understanding phenotypes and sub-types of asthma. Improving the drug development process. Pre-competitive pre-clinical and clinical research. Abstract: Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes (U-BIOPRED) was initiated in the first year of the Innovative Medicines Initiative (IMI). It was an ambitious plan to tackle the understanding of asthma through an integration of clinical and multi-'omics approaches that necessitated the bringing together of industry, academic, and patient representatives because it was too large to be managed by any one of the partners in isolation. It was a novel experience for all concerned. In this review, we describe the main features of the U-BIOPRED experience from the industry perspective. We list some of the key advantages and learnings from the perspective of the authors, and also improvements that we feel could be made in future projects. Teaser: The U-BIOPRED program within the Innovative Medicine Initiatives (IMI) attempted to address fundamental issues around the lack of disease understanding in asthma. This review summarises key issues, learnings, and successes of running the U-BIOPRED program from the industry perspective.